Plasmonic Amyloid Tactoids (Adv. Mater. 51/2021). Issue 51 (22nd December 2021) - Yuan, Ye; Almohammadi, Hamed; Probst, Julie; Mezzenga, Raffaele
Abstract : Liquid‐Crystalline Droplets In article number 2106155, Raffaele Mezzenga and co‐workers demonstrate a schematic representation of amyloid fibrils confined within a liquid‐crystalline droplet formed by liquid–liquid‐crystalline phase separation, and organized in a chiral nematic conformation, capable of guiding the spatial and orientational distribution of functionalized gold nanorods added to the colloidal system.